Structural damage identification and location using grammian matrices - Bueno, D. D. [UNESP]; Marqui, C. R. [UNESP]; Lopes, V. [UNESP]; Brennan, M. J. [UNESP]; Inman, Daniel J. (IOS Press, 2012)
In this paper, an approach using observability and controllability grammian matrices is proposed to determine if structural damage has occurred together with an estimate of its location. The theory is outlined and simulations are carried out on a simple structure to demonstrate the method. Experimental tests were also carried out to demonstrate the validity of the approach using real signals. The dynamic properties of the structure are identified using the eigensystem realization algorithm (ERA) and a reduced order state-space model of the system subsequently constructed. Either the observability or controllability grammians can then be used depending on the number of sensors available. It is shown that these are sensitive to both the degree and location of the damage and offer promise for structural health monitoring applications.